Socioeconomic factors differentiating maternal and child health-seeking behavior in rural Bangladesh: A cross-sectional analysis - Becker Stan; Shah Nirali M; Amin Ruhul (BMC, 2010)
Abstract Background There has been an increasing availability and accessibility of modern health services in rural Bangladesh over the past decades. However, previous studies on the socioeconomic differentials in the utilization of these services were based on a limited number of factors, focusing either on preventive or on curative modern health services. These studies failed to collect data from remote rural areas of the different regions to examine the socioeconomic differentials in health-seeking behavior. Methods Data from 3,498 randomly selected currently married women from three strata of households within 128 purposively chosen remote villages in three divisions of Bangladesh were collected in 2006. This study used bivariate and multivariate logistic analyses to examine both curative and preventive health-seeking behaviors in seven areas of maternal and child health care: antenatal care, postnatal care, child delivery care, mother's receipt of Vitamin A postpartum, newborn baby care, care during recent child fever/cough episodes, and maternal coverageby tetanus toxoid (TT). Results A principal finding was that a household's relative poverty status, as reflected by wealth quintiles, was a major determinant in health-seeking behavior. Mothers in the highest wealth quintile were significantly more likely to use modern trained providers for antenatal care, birth attendance, post natal care and child health care than those in the poorest quintile (χ2, p < 0.01). The differentials were less pronounced for other factors examined, such as education, age, and the relative decision-making power of a woman, in both bivariate and multivariate analyses. Conclusion Within rural areas of Bangladesh, where overall poverty is greater and access to health care more difficult, wealth differentials in utilization remain pronounced. Those programs with high international visibility and dedicated funding (e.g., Immunization and Vitamin A delivery) have higher overall prevalence and a more equitable distribution of beneficiaries than the use of modern trained providers for basic essential health care services. Implications of these findings and recommendations are provided.